The Rights of an Apostate Wife Whom Her Husband Divorces Based on The Judgment of Islamic Religious Judges - Nurlaini Milo Siregar; Muhammad Syukri Albani; Imam Yazid (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This study delves into the analysis of the rights of apostate wives divorced by their husbands, with a specific focus on the decision rendered by the Klaten Religious Court with case number 0082/Pdt.G/2022/PA. Klt. The research aims to address existing gaps in Marriage Law No. 1 of 1974, as amended by Law No. 16 of 2019, and the compilation of Islamic law, particularly regarding the need for detailed regulations on the legal consequences following post-divorce due to apostasy (riddah). Employing a normative juridical methodology through literature research, the study adopts a comparative approach to analyze the data. The findings reveal that the Klaten Religious Court's decision, registered as 0082/Pdt.G/2022/PA, recognizes apostasy as a valid ground for the dissolution of marriage, in accordance with Article 114, letter (h) of the compilation of Islamic Law listing reasons for marriage dissolution. The court, acknowledging apostasy as grounds for termination, granted the apostate wife the rights to iddah and Mut'ah. Consequently, the ex-wife is entitled to assert her rights. In conclusion, the decision of the Klaten Religious Court addresses the rights of apostate wives post-divorce, yet underscores the necessity for a more detailed and comprehensive legal framework to guide similar cases and safeguard the rights of the involved parties.